History of indonesian archipelago culture and civilization: from hindubuddha, islam, colonialism to local wisdom and gender. (Journal of Communication and Multidisciplinary studies, 2026)
Kalimantan is a region rich in cultural heritage and traditions, lived out by multi-ethnic communities such as the Dayak, Banjar, Kutai, and Malay. Local wisdom and customs play a crucial role in regulating social and spiritual life, as well as fostering a harmonious relationship between humans and nature. Values such as mutual cooperation, respect for nature, customary law, and religious and social rituals form the foundation of the cultural identity of the people of Kalimantan. However, modernization, globalization, and the exploitation of natural resources present serious challenges to the preservation of these traditions. Therefore, preservation efforts through education, cultural documentation, and strengthening the role of indigenous communities are crucial to maintaining the sustainability of Kalimantan's cultural heritage as part of Indonesia's national cultural heritage.